Improving Scientific Paper Writing Skills Based on Classroom Action Research of Teachers at SMP N 9 Purwokerto - Lalita Melasarianti; Etin Pujihastuti; Arfin Deri Listiandi; Didik Rilastiyo Budi; Uki Hares Yulianti; Nur Indah Sholikhati (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Several statements regarding the low condition of teachers' skills in writing scientific papers, such as research conducted by Melasarianti, Yulianti, and Marahayu (2023) found several obstacles to the implementation of the independent curriculum, namely teachers rarely conduct scientific research to innovate learning, whether in methods, techniques, media, models, materials, or even stimuli in learning. Observations and interviews with the Principal of State Junior High School 9 Purwokerto Drs. Herry Nuryanto Widodo and several other teachers revealed that the awareness of teachers at State Junior High School 9 Purwokerto in writing scientific papers is still low. Their knowledge of classroom action research (CAR) is also not optimal. Based on the situation that occurs in junior high school teachers in the Banyumas Regency area, especially at State Junior High School 9 Purwokerto, this community service activity was carried out. The implementation method in this activity is expected to be able to improve the scientific writing skills of State Junior High School 9 Purwokerto teachers based on Classroom Action Research (CAR). The results of this activity include: 1) increasing knowledge and information regarding writing scientific papers, 2) increasing knowledge regarding the use of Mendeley and AI as support for writing scientific papers, and 3) increasing knowledge regarding several accredited journals.